Techno -economy of lithic raw materials in Piedmont (north-western Italy). A first life-like scenario - Sara Daffara; Gabriele Luigi Francesco Berruti; Sandro Caracausi; Maite García-Rojas; Marta Arzarello (Journal of Lithic Studies, 2023)
Data about Palaeolithic peopling, settlement dynamics and techno-economy of the south-western margin of the Alpine region are sketchy. In this area, the lack of systematic research and the scarcity of lithic raw materials, spread the idea that Piedmont was not inhabited during Palaeolithic. In 2009, the re-starting of the excavations at the Ciota Ciara cave, gave rise to new questions and to the development of research projects at a regional scale.